Minimalist Perspective on Legal Communication: A Case Study of English to Urdu Translation of Punjab Laws - Naumana Kanwal; Muhammad Javed Iqbal; Mariam Mushtaq (Register Journal, 2022)
Syntactic choices and complexity reduction make translation communicative for the readers. This paper underscores the syntactic choices as well as complexity reduction in Urdu translation of Punjab laws in English. The study focuses on legal communication in a minimalistic perspective. It draws upon the theory of minimalism proposed by Chomsky (1993), along with the three-stage model by Nida and Taber (1969). Data is analyzed by employing Burton’s (2021) clausal analysis. The legal data used for the research comprises Punjab laws in English and their Urdu translation. The findings reveal minimalism as a useful strategy in the translation process for reducing structure complexity and making the translation understandable to laypeople. The study is beneficial to English-Urdu translators since it instructs them on how to make their translations communicative, especially when dealing with legal texts. It is also useful for academics in the field of Translation Studies who are working on minimalist views.Keywords: minimalism, complexity reduction, legal translation, syntactic choices, communication